Seeing It Helps: Movement-related Back Pain Is Reduced by Visualization of the Back During Movement - Wand, B.; Tulloch, V.; George, P.; Smith, Anne; Goucke, R.; O'Connell, N.; Moseley, L. (Lippincott Williams & Wilkins, 2012)
Objectives: The aim of this study was to determine whether visualization of the back influenced parameters of movement-related pain in people with chronic nonspecific low back pain. Methods: We used a randomized cross-over experiment in which 25 participants performed repeated lumbar spine movements under 2 conditions. In the visual feedback condition, patients were able to visualize their back as it moved by the use of mirrors. In the control condition, the mirror was covered so no visualization of the back was possible. Results: The average postmovement pain intensity after participants had moved with visual feedback was less (35.5±22.8 mm) than when they moved without visual feedback (44.7±26.0 mm). This difference was statistically significant (mean difference=9.3, 95% confidence interval: 2.8-15.7 F(1,22)=8.82, P=0.007). The average time to ease after participants had moved with visual feedback was shorter (44.5 s±53.8) than when they moved without visual feedback (94.4 s±80.7). This difference was also statistically significantly (mean difference=49.9, 95% confidence interval: 19.3-80.6, F(1,22)=8.82, P=0.003). Discussion: Patients with chronic nonspecific low back pain reported less increase in pain and faster resolution of pain when moving in an environment that enabled them to visualize their back. This is consistent with emerging research on the use of mirror visual feedback in other long-standing pain problems and suggests that similar lines of inquiry may be worth pursuing in the chronic nonspecific low back pain population.